2013
DOI: 10.5433/1679-0359.2013v34n3p1141
|View full text |Cite
|
Sign up to set email alerts
|

Pulp fruit added to culture medium for in vitro orchid development

Abstract: As an additive in in vitro culture media, fruits have a great potential for facilitating economical orchid production because of lower technology requirements and the ease of obtaining raw materials to formulate culture media. We studied the in vitro growth of Cattleya bicolor Lindl. grown in a simplified culture medium supplemented with different kinds of fruit pulp. The experimental design was completely randomised, with eight seedlings per replication and ten replications per treatment, for a total of 80 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The combination of VW and 150 g L -1 of the banana extract (BE) was the best regeneration medium for D. Dian Agrihorti EC to produce the best performances of plantlets. Optimal regeneration indicated via better shoot and root growth was due to banana nutrition contents, i.e., glucose, carbohydrate, hormones, and vitamins of A, B, C, E, and K involving B1 or thiamine (De Souza et al, 2013;Bayraktar et al, 2015;Hapsari and Lestari, 2016;Mustika and Semiarti, 2021). Thiamine is a type of vitamin B1 that can stimulate cell division in the shoot and root so that the shoots and roots can grow faster due to its important role as a cofactor in metabolism activities and regulatory system (Subki et al, 2010;De Souza et al, 2013;Humaira et al, 2015).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of VW and 150 g L -1 of the banana extract (BE) was the best regeneration medium for D. Dian Agrihorti EC to produce the best performances of plantlets. Optimal regeneration indicated via better shoot and root growth was due to banana nutrition contents, i.e., glucose, carbohydrate, hormones, and vitamins of A, B, C, E, and K involving B1 or thiamine (De Souza et al, 2013;Bayraktar et al, 2015;Hapsari and Lestari, 2016;Mustika and Semiarti, 2021). Thiamine is a type of vitamin B1 that can stimulate cell division in the shoot and root so that the shoots and roots can grow faster due to its important role as a cofactor in metabolism activities and regulatory system (Subki et al, 2010;De Souza et al, 2013;Humaira et al, 2015).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…Optimal regeneration indicated via better shoot and root growth was due to banana nutrition contents, i.e., glucose, carbohydrate, hormones, and vitamins of A, B, C, E, and K involving B1 or thiamine (De Souza et al, 2013;Bayraktar et al, 2015;Hapsari and Lestari, 2016;Mustika and Semiarti, 2021). Thiamine is a type of vitamin B1 that can stimulate cell division in the shoot and root so that the shoots and roots can grow faster due to its important role as a cofactor in metabolism activities and regulatory system (Subki et al, 2010;De Souza et al, 2013;Humaira et al, 2015). Vitamins are also necessary for the growth of cells that are still actively dividing because they act as catalysts in metabolism (Humaira et al, 2015;Hapsari and Lestari, 2016).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…For roots fresh and dry mass, superior values were observed for the simplified medium, under light source L4. In a study with simplified culture media with fruit pulps, for the in vitro growth of Cattleya bicolor, Souza et al (2013) found no differences for roots and canopy dry mass when comparing the ½ MS medium to the simplified medium composed by 'Nanica' banana pulp. This shows that the reaction to growth also depends on the interaction between species and culture medium.…”
Section: Resultsmentioning
confidence: 99%
“…In the in vitro propagation of orchids, the modified MS medium (MURASHIGE;SKOOG, 1962) has been used by most plants biofactories (FARIA et al, 2002;MORAES et al, 2005), as well as several simplified media based on commercial fertilizers and organic components such as banana pulp, tomato pulp and coconut water (ARAÚJO et al, 2006;STANCATO et al, 2008;BAQUE et al, 2011;COLOMBO et al, 2012;SU et al, 2012;SOUZA et al, 2013;FAVETTA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that the addition of some organic substances in medium culture, such as fruit extract can enhance plantlet growth. The fruit extracts in culture medium contain many nutrients providing hormones and plant growth regulator useful to increase plant growth (Souza et al 2013). The addition of banana extract (50 g/L) in culture medium has been shown to promote protocormlike bodies (PLBs) viability (Yulianti et al 2016) Musa acuminata x Musa balbisiana is one of the Indonesian banana cultivars called "Pisang Raja" that Indonesian people widely consume.…”
Section: Introductionmentioning
confidence: 99%